Intestinal Alkaline Phosphatase Prevents Sulfate Reducing Bacteria-Induced Increased Tight Junction Permeability by Inhibiting Snail Pathway - Singh, Sudha B.; Coffman, Cristina N.; Varga, Matthew G.; Carroll-Portillo, Amanda; Braun, Cody A.; Lin, Henry C. (Frontiers in Cellular and Infection Microbiology, 2022)
Tight junctions (TJs) are essential components of intestinal barrier integrity and protect the epithelium against passive paracellular flux and microbial translocation. Dysfunctional TJ leads to leaky gut, a condition associated with diseases including inflammatory bowel disease (IBD). Sulfate-reducing bacteria (SRB) are minor residents of the gut. Increased number of Desulfovibrio, the most predominant SRB, is observed in IBD and other diseases associated with leaky gut. However, it is not known whether Desulfovibrio contributes to leaky gut. We tested the hypothesis that Desulfovibrio vulgaris (DSV) may induce intestinal permeability in vitro. Snail, a transcription factor, disrupts barrier function by affecting TJ proteins such as occludin. Intestinal Alkaline Phosphatase (IAP), a host defense protein, protects epithelial barrier integrity. We tested whether DSV induced permeability in polarized Caco-2 cells via snail and if this effect was inhibited by IAP. Barrier integrity was assessed by measuring transepithelial electric resistance (TEER) and by 4kDa FITC-Dextran flux to determine paracellular permeability. We found that DSV reduced TEER, increased FITC-flux, upregulated snail protein expression, caused nuclear translocation of snail, and disrupted occludin staining at the junctions. DSV-induced permeability effects were inhibited in cells knocked down for snail. Pre-treatment of cells with IAP inhibited DSV-induced FITC flux and snail expression, and DSV-mediated disruption of occludin staining. These data show that DSV, a resident commensal bacterium, can contribute to leaky gut and that snail may serve as a novel therapeutic target to mitigate DSV-induced effects. Taken together, our study suggests a novel underlying mechanism of association of Desulfovibrio bloom with diseases with increased intestinal permeability. Our study also underscores IAP as a novel therapeutic intervention for correcting SRB-induced leaky gut via inhibition of snail.